Biodegradation of monocrotophos by Brucella intermedia Msd2 isolated from cotton plant - Shazmin, undefined; Ahmad, Siti Aqlima; Naqvi, Tatheer Alam; Munis, Muhammad Farooq Hussain; Javed, Muhammad Tariq; Chaudhary, Hassan Javed (Springer Dordrecht, 2023)
Widespread and inadequate use of Monocrotophos has led to several environmental issues. Biodegradation is an ecofriendly method used for detoxifcation of toxic monocrotophos. In the present study, Msd2 bacterial strain was isolated from the cotton plant growing in contaminated sites of Sahiwal, Pakistan. Msd2 is capable of utilizing the monocrotophos (MCP) organophosphate pesticide as its sole carbon source for growth. Msd2 was identifed as Brucella intermedia on the basis of morphology, biochemical characterization and 16S rRNA sequencing. B. intermedia showed tolerance of MCP up to 100 ppm. The presence of opd candidate gene for pesticide degradation, gives credence to B. intermedia as an efective bacterium to degrade MCP. Screening of the B. intermedia strain Msd2 for plant growth promoting activities revealed its ability to produce ammonia, exopolysaccharides, catalase, amylase and ACC-deaminase, and phosphorus, zinc and potassium solubilization. The optimization of the growth parameters (temperatures, shaking rpm, and pH level) of the MCP-degrading isolate was carried out in minimal salt broth supplemented with MCP. The optimal pH, temperature, and rpm for Msd2 growth were observed as pH 6, 35 °C, and 120 rpm, respectively. Based on optimization results, batch degradation experiment was performed. Biodegradation of MCP by B. intermedia was monitored using HPLC and recorded 78 degradation of MCP at 100 ppm concentration within 7 days of incubation. Degradation of MCP by Msd2 followed the frst order reaction kinetics. Plant growth promoting and multi-stress tolerance ability of Msd2 was confrmed by molecular analysis. It is concluded that Brucella intermedia strain Msd2 could be benefcial as potential biological agent for an efective bioremediation for polluted environments.